Numerical simulations of RC hollow piers under horizontal cyclic loading - P. Delgado (2011)
This article addresses numerical simulations of experimentally tested RC hollow-section piers prone to shear problems under cyclic loading. Detailed nonlinear modeling was applied with 3D FEM dis-cretization using a damage model for concrete and a cyclic behavior model for steel bars represented by uniaxial elements Analyses were supported by parameter calibration based on experimental pier test data. The results confirmed the adequacy of the modeling strategy for simulating shear effects in these piers.